(untitled) (Research, Society and Development, 2021)
The present study aims to identify the principal causes of self-violence between medical students, also identifying its possible consequences. The objective was to enlighten the subject, in order to contribute to its prevention. This review’s literature was obtained from SCIELO and Lilacs databases, using as descriptors “medical students and suicide, medical students and alcohol, medical students and drugs”. The inclusion criteria was articles published between 2015 and 2020, in English, Spanish and Portuguese; the exclusion criteria was compensated articles, literature reviews and comments, texts regarding residents and doctors in addiction to articles that studied other students from other courses. It was found a correlation between the suicide ideation, psychiatric disorders such as depression and anxiety, and licit or illicit substance abuse among the medical students evaluated. Mid the most cited causes there are psychological exhaustion, the course’s extensive workload, sleep deprivation, stress and insecurity. Therefore, the conclusion is that the overload of the medical students affects both the mental health and the academical performance, conducting them into practicing violence agains them selfs, as substance abuse or refusal of psychological help.